2010
DOI: 10.9755/ejfa.v22i6.4660
|View full text |Cite
|
Sign up to set email alerts
|

Bread and durum wheat tolerance under heat stress: A synoptical overview

Abstract: Temperature and nutrition are two major components of environmental variation that provide significant limitations to a successful crop production. Increasing temperatures during grain filling interacts, at a metabolic level, with growth duration and filling rates, as well as with grain maturity and quality. At a nutritional level, temperature is also linked to uptake and translocation rates to roots and shoots tissues, which determines crop production. Nevertheless, these interacting effects are closely relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 144 publications
(202 reference statements)
2
16
0
Order By: Relevance
“…biuncialis. The bread and durum wheat tolerance to heat stress was determined by Dias et al [131] which confirmed that increased temperatures during grain filling stage interacts at a metabolic level, growth duration and filling rates, as well as with grain maturity and quality. Screening of wheat germplasm for heat tolerance at terminal growth stage was done by Rehman et al [100].…”
Section: Thermo-tolerance In Wheatmentioning
confidence: 71%
“…biuncialis. The bread and durum wheat tolerance to heat stress was determined by Dias et al [131] which confirmed that increased temperatures during grain filling stage interacts at a metabolic level, growth duration and filling rates, as well as with grain maturity and quality. Screening of wheat germplasm for heat tolerance at terminal growth stage was done by Rehman et al [100].…”
Section: Thermo-tolerance In Wheatmentioning
confidence: 71%
“…In semi‐arid climates air temperatures during grain filling represent a typical constraint for wheat production (Dias & Lidon, ). In greenhouse, the effect of post‐anthesis heat stress was strongly exacerbated.…”
Section: Discussionmentioning
confidence: 99%
“…I G U R E 7 Instantaneous water use efficiency (WUE, μmol CO 2 mmol H 2 O −1 ) throughout grain filling of durum wheats under open-field condition (C) and greenhouse heat stress (HS) (means ± SD) [Colour figure can be viewed at wileyonlinelibrary.com] F I G U R E 8 Kernel dry matter accumulation (mg) during grain filling of durum wheats under open-field condition (C) and greenhouse heat stress (HS)In semi-arid climates air temperatures during grain filling represent a typical constraint for wheat production(Dias & Lidon, 2010). In greenhouse, the effect of post-anthesis heat stress was strongly exacerbated.…”
mentioning
confidence: 99%
“…Regression analysis and clustering based on local LD decay confirmed that these associations were distributed over 12 loci (Table 2 and Table S6). Chromosome 1A had the highest number of MTAs (27) while chromosome 4A had the lowest (6).…”
Section: Markers Associated To Heat Stress Tolerancementioning
confidence: 97%
“…High temperatures at the time of flowering cause floret sterility via pollen dehiscence [2], decrease photosynthetic capacity by drying the green tissues, and reduce starch biosynthesis [1,3]. These in turn result in a negative effect on grain number and weight [4][5][6][7]. The optimum growing temperature for wheat during pollination and grain filling phases is 21 • C [8,9], and for each increase of 1 • C above it is estimated a decline of 4.1% to 6.4% in yield [10].…”
Section: Introductionmentioning
confidence: 99%